Epizootic situation for brucellosis in the Russian Federation (review) - O. I. Zakharova; O. A. Burova; I. V. Iashin; A. A. Blokhin; О. И. Захарова; О. А. Бурова; И. В. Яшин; А. А. Блохин (Agricultural Science Euro-North-East, 2023)
The World Health Organization (WHO) considers brucellosis to be one of the most dangerous and spread zoonosis in the world. The aim of the review is to summarize the current scientific data on the brucellosis in animals, to analyze the epizootic situation in the Russian Federation, Arctic Zone included, and to define the key factors of animal protection against the infection. The epizootic situation for brucellosis in farm animals, which are carriers of the three main pathogens of brucellosis, is an urgent epidemiological problem. Their widespread occurrence is the factor determining the world-wide distribution of pathogens in most countries that indicates for the importance of control the brucellosis on an international scale. In Russia, a high epizootic risk of the spread of the disease is observed in the regions of the Volga, Southern and North Caucasian Federal Districts, in southern Siberia and Far East as well as in the Arctic. Brucellosis has the same epizootic and epidemiological significance in the Arctic regions considering the national food preferences of the peoples of the Far North. In the Russian Arctic, epizootic foci of brucellosis in cattle and reindeer have been identified and evidence of the epidemiological significance and ecological association of B. suis with the reindeer population has been presented. Specific prophylaxis of brucellosis is based on the use of vaccines. However, the problem of reindeer vaccination has not been finally resolved. Бруцеллез рассматривается Всемирной организацией здравоохранения (ВОЗ) как один из наиболее опасных и распространенных зоонозов в мире. Цель обзора – обобщить актуальные научные данные по бруцеллезу животных, проанализировать эпизоотическую ситуацию в Российской Федерации, в том числе Арктической зоне, и определить ключевые факторы стратегии защиты животных от инфекции. Эпизоотическая ситуация по бруцеллезу сельскохозяйственных животных, которые являются переносчиками трех основных его возбудителей, имеет выраженную эпидемиологическую значимость. ...